2007
DOI: 10.1200/jco.2007.25.18_suppl.5005
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel plus prednisone or mitoxantrone plus prednisone for advanced prostate cancer: Updated survival of the TAX 327 study

Abstract: 5005 Background: The TAX-327 study compared 3 weekly docetaxel (D3), weekly docetaxel (D1) or mitoxantrone (M), each with prednisone (P) for 1006 patients (pts) with metastatic hormone resistant prostate cancer (mHRPC). The original analysis, undertaken in August 2003 when 557 deaths had occurred, showed significantly better survival and response rates for pain, PSA and quality of life for D3 when compared with M (Tannock et al, NEJM 2004;351:1502–12). Here we present the updated survival analysis. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 0 publications
2
120
1
6
Order By: Relevance
“…Additional hormone manipulations such as antiandrogen withdrawal, complete androgen blockade and the use of oestrogen–progesterone derivatives have been employed with conflicting results [5,6]. The presence of unfavourable conditions such as the onset of tumour‐related symptoms or of progressive bone or parenchyma metastases justifies the resort to a docetaxel‐based chemotherapy for cytoreduction [7–9]. It must be emphasized that sometimes elderly patients who are unfit because of concomitant diseases are not suitable for chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Additional hormone manipulations such as antiandrogen withdrawal, complete androgen blockade and the use of oestrogen–progesterone derivatives have been employed with conflicting results [5,6]. The presence of unfavourable conditions such as the onset of tumour‐related symptoms or of progressive bone or parenchyma metastases justifies the resort to a docetaxel‐based chemotherapy for cytoreduction [7–9]. It must be emphasized that sometimes elderly patients who are unfit because of concomitant diseases are not suitable for chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In an extended survival analysis of the TAX 327 study , in which patients with symptomatic mCRPC or evident disease progression were included, docetaxel could bring about significantly longer median OS (19.2 months) in patients when compared with mitoxantrone (16.3 months). The OS advantage of docetaxel was also consistent across varied patient subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated improved survival in patients treated with the 3‐weekly docetaxel and prednisone regimen compared to the mitoxantrone and prednisone arm. In the most recent update 8 the survival benefit of 3‐weekly docetaxel has been shown to persist (median survival 19.2 vs 17.8 vs 16.3 months for 3‐weekly docetaxel, weekly docetaxel and mitoxantrone respectively, P = 0.004). The corresponding 3‐year survival rate was 17.9, 16.7 and 13.7%, respectively.…”
Section: First‐line Chemotherapymentioning
confidence: 99%